If $a^2 +b^2 + 2b + 4a + 5 = 0$, then the value of $\frac{2a-3b}{2a+3b}$ is equal to: |
$\frac{1}{7}$ $\frac{2}{7}$ $\frac{3}{7}$ $\frac{2}{5}$ |
$\frac{1}{7}$ |
If $a^2 +b^2 + 2b + 4a + 5 = 0$ We know that, (a + b)2 = a2 + b2 + 2ab a2 + b2 + 2b + 4a + 5 = 0, = a2 + 4a + b2 + 2b + 5 = 0 = a2 + 4a + 4 + b2 + 2b + 1 = 0 = (a + 2)2 + (b + 1)2 = 0 So, a + 2 = 0 = a = -2 And, b + 1 = 0 = b = -1 Put these values in the desired equation, $\frac{2a-3b}{2a+3b}$ = $\frac{2(-2)-3(-1)}{2(-2)+3(-1)}$ = \(\frac{1}{7}\) |